2009
DOI: 10.1130/g25680a.1
|View full text |Cite
|
Sign up to set email alerts
|

Velocity of vertical fluid ascent within vein-forming fractures

Abstract: Quartz-albite-calcite veins in metamorphic rocks of the Sanbagawa belt, Japan, contain sugary mosaics of equant quartz grains <0.01-1.6 mm in size (blocky texture). The quartz crystals show euhed ral to subhedral double-terminated crystal shape, and concentric growth zoning, indicating suspension in aqueous fl uid during crystal growth until formation of a framework within the crack. Such a crystallization process is only possible when downward crystal settling is balanced by upward fl uid fl ow. Application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 23 publications
3
21
0
Order By: Relevance
“…6a and d. It is difficult to know which mechanism operates in natural blocky quartz veins: direct nucleation of quartz from solution or recrystallization from opaline silica. However, some blocky veins consist of euhedral quartz crystals that show concentric growth zoning, coexisting with fine-grained albite (Okamoto et al, 2008;Okamoto and Tsuchiya, 2009), similar to that seen in the M-gr run in the present study.…”
Section: Implications For Quartz Vein Formationsupporting
confidence: 74%
See 1 more Smart Citation
“…6a and d. It is difficult to know which mechanism operates in natural blocky quartz veins: direct nucleation of quartz from solution or recrystallization from opaline silica. However, some blocky veins consist of euhedral quartz crystals that show concentric growth zoning, coexisting with fine-grained albite (Okamoto et al, 2008;Okamoto and Tsuchiya, 2009), similar to that seen in the M-gr run in the present study.…”
Section: Implications For Quartz Vein Formationsupporting
confidence: 74%
“…In the crustal conditions, the high degree of supersaturation at the sites of vein formation is realized by fluid ascent with sufficiently high flow rate relative to the precipitation rate of silica (Rimstidt and Barnes, 1980), or by a pressure drop related to seismicity (Fournier, 1985). Some studies on blocky veins estimated the extremely high ascent rates in the order of 0.1-1 m s À1 during the vein formation (Bons, 2001;Okamoto and Tsuchiya, 2009). Therefore, the fractures to produce blocky veins could act as the dominant fluid pathways in the Earth's crust.…”
Section: Implications For Quartz Vein Formationmentioning
confidence: 98%
“…An essential feature of such a mechanism is that, irrespective of the mean-stress gradient, hydraulic connectivity must be maintained over a vertical interval that is large enough to generate the effective pressures necessary to drive the deformation. Both self-propagating domains of fluid-filled fractures (Gold and Soter 1985) and individual hydrofractures (Rubin 1995;Nakashima 1995;Okamoto and Tsuchiya 2009) have been proposed as the mechanism for such flow. These models suppose that the fractures are closed at depth, i.e., compacted, by the elastic response of the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…In the above KIE Experimental data are from Hazen et al (1989) and Rastsvetaeva et al (2009) However, a special kind of quartz, the so-called Herkimer ''diamond,'' which is extremely pure, is thought to be precipitated under an equilibrium condition. Okamoto and Tsuchiya (2009) suggested that this kind of quartz must be slowly grown in an upward fluid flow to form such a special double-terminated crystal. This also implies a huge solution reservoir for it (e.g., ruling out isotope reservoir effect).…”
Section: Si Isotope Fractionation Between Quartz and Solutionmentioning
confidence: 99%